Relationship between Body Mass Index and Health-Related Physical Fitness Components in HIV-Diagnosed Children and Adolescents - João Antônio Chula de Castro; Luiz Rodrigo Augustemak de Lima; Diego Augusto Santos Silva (MDPI AG, 2024)
Background/Objectives: There is a need to monitor physical fitness in HIV-diagnosed children and adolescents, and body mass index (BMI) could be an option for this due to its usability for assessing nutritional status and fat mass. The present study aimed to explore the relationship between BMI and physical fitness in HIV-diagnosed children and adolescents. Methods: A cross-sectional study was conducted with 86 HIV-diagnosed children and adolescents aged 5-15, with participants from two research protocols (Study I, n = 65; Study II, n = 21). Physical fitness was assessed through body composition (anthropometric measurements and dual energy X-ray absorptiometry), cardiorespiratory fitness (peak oxygen consumption [VO2peak]), muscle strength/endurance (handgrip strength, standing broad jump, and abdominal and modified push-up endurance), and flexibility (sit-to reach test). The relationship between BMI and physical fitness components was analyzed through correlation and simple and multiple linear regression analysis. Results: Eutrophic participants (mean age 11.44 ± 2.20) presented a normal fat mass percentage and overweight participants (mean age 11.50 ± 2.54) presented adequate handgrip strength. The adjusted models could explain 71% of fat-free mass, 57% of fat mass percentage, 70% of bone mineral content, 72% of bone mineral density, and 52% of handgrip strength. Conclusions: Increases in BMI were associated with increases in fat-free mass, fat mass percentage, bone mineral content, bone mineral density, and handgrip strength. BMI was capable of distinguishing those presenting a normal fat mass percentage and those presenting adequate handgrip strength.